Effect of dexmedetomidine as adjuvant in supraclavicular block for upper limb orthopedic surgeries - Modh, Dixitkumar B.; Parmar, Manthan; Solanki, Shilpin (International Surgery Journal, 2017)
Background: Dexmedetomidine has anxiolytic, sedative, hypnosis, analgesic, antisialogogue and sympatholytic properties which render it suitable as an adjuvant. Hence this study was aimed to prove its efficacy as an adjuvant to lignocaine and bupivacaine for supraclavicular block in patients undergoing orthopedic upper limb surgeries. Other objectives of the study were to evaluate and compare the onset and duration of sensory and motor block as well as total analgesia, to compare effect on hemodynamic and respiratory parameters and to study any adverse effect associated with dexmedetomidine as adjuvant. Methods: Sixty patients of ASA physical status class I & II of elective upper limb forearm orthopedic surgeries were selected in our study. Patients in group NS (n=30) received 10 ml lignocaine 2% + 20 ml bupivacaine 0.5% + 1 ml normal saline for supraclavicular block and group D (n=30) received 10 ml lignocaine 2% + 20 ml bupivacaine 0.5% + 1 µg/kg of Dexmedetomidine for the same block. The onset and duration of sensory and motor block, total duration of analgesia, need of rescue analgesic postoperatively, postoperative VAS score was assessed and compared between the two groups. Results: Demographic data and surgical characteristics are comparable in both the groups. The onset of sensory and motor block was significantly lower (p <0.05) in group D than in group NS. The duration of sensory and motor block was significantly higher (p <0.01) in group D when compared to group NS. The duration of analgesic requirement postoperatively was significantly higher (p <0.01) in group D than group NS. No significant change in observations was made for hemodynamic parameters in both the groups. Conclusions: Dexmedetomidine can be considered as an adjuvant to lignocaine and bupivacaine mixture for excellent quality supraclavicular block without any side effects and provide good sedation in patients undergoing orthopedic upper limb surgeries.